Improving of Educational Programs for the Formation of Information and Communication Competence of Teachers - Grygorenko, Tetyana V. (2021)
The educational process has to manage the demand to meet all modern requirements for educational activities, which cannot be realized without proper formation of information and communication competence of teachers. The aim of this study is to identify the modern condition of formation and practice of information and communication competence of teachers in the paradigm of Ukrainian educational realities. Our task is to compare them with the practice of leading European countries and predicted directions of education-2030 with a focus on improving digital competencies of a teacher as an organizer of educational activities. A prominent place in the process of increasing the information and communication competence of teachers is occupied by the appropriate conditions for creating an information and communication environment for the formation of the future teacher of higher education institution. The methods of collection, analysis and systematization, data generalization concerning the modern condition of development of competencies in the usage of information and computer technologies by Ukrainian teachers and the whole world were used in the process of the study. An assessment of the readiness of Ukrainian teachers to provide online education has been made in the context of a world coronavirus pandemic. According to world experts, the pandemic has made radical and irreversible changes in modern ideas about learning, the role of teachers in the educational process, the set of competencies of teachers in the XXI century.